Effectiveness of BBIBP-CorV, BNT162b2 and mRNA-1273 vaccines against hospitalisations among children and adolescents during the Omicron outbreak in Argentina: A retrospective cohort study - Soledad González; Santiago Olszevicki; Alejandra Gaiano; Ana Nina Varela Baino; Lorena Regairaz; Martín Salazar; Santiago Pesci; Lupe Marín; Verónica V. González Martínez; Teresa Varela; Leticia Ceriani; Enio Garcia; et al. (Elsevier, 2022)
Summary: Background: Although paediatric clinical presentations of COVID-19 are usually less severe than in adults, serious illness and death have occurred. Many countries started the vaccination rollout of children in 2021; still, information about effectiveness in the real-world setting is scarce. The aim of our study was to evaluate vaccine effectiveness (VE) against COVID-19-associated-hospitalisations in the 3-17-year population during the Omicron outbreak. Methods: We conducted a retrospective cohort study including individuals aged 3-17 registered in the online vaccination system of the Buenos Aires Province, Argentina. mRNA-1273 and BNT162b2 were administered to 12-17-year subjects; and BBIBP-CorV to 3-11-year subjects. Vaccinated group had received a two-dose scheme by 12/1/2021. Unvaccinated group did not receive any COVID-19 vaccine between 12/14/2021 and 3/9/2022, which was the entire monitoring period. Vaccine effectiveness (VE) against COVID-19-associated hospitalisations was calculated as (1-OR)x100. Findings: By 12/1/2021, 1,536,435 individuals aged 3-17 who had received zero or two doses of SARS-CoV-2 vaccines were included in this study. Of the latter, 1,440,389 were vaccinated and 96,046 not vaccinated. VE were 78.0%[68.7-84.2], 76.4%[62.9-84.5] and 80.0%[64.3-88.0] for the entire cohort, 3-11-year (BBIBP-CorV) subgroup and 12-17 (mRNA vaccines) subgroup, respectively. VE for the entire population was 82.7% during the period of Delta and Omicron overlapping circulation and decreased to 67.7% when Omicron was the only variant present. Interpretation: This report provides evidence of high vaccine protection against associated hospitalisations in the paediatric population during the Omicron outbreak but suggests a decrease of protection when Omicron became predominant. Application of a booster dose in children aged 3-11-year warrants further consideration. Funding: None.